Analysis of Traditional Art Content of The Dayak Ngaju Tribe “Karungut” as Strengthening the Emotional Social Education of Students in Palangka Raya - Prawati, Melinda; Sion, Holten; Fransiska, Carolina (Jurnal Pendidikan Edutama, 2025)
Education aims to optimally develop the human potential possessed by individuals. The art of " karungut" is a traditional art form of the Dayak Ngaju, through vocal performance. This research to analyze and describe the content of the "karungut" that can be utilized to strengthen the socio-emotional education of students in Palangka Raya. The research method used is qualitative with a case study. Data were collected through interviews, observation, and documentation. The respondents of the research consisted of 3 “karungut” artists, 6 elementary school teachers, and 10 students. The data analysis used was the interactive analysis. The results showed that “karungut” contains the following aspects: (1) self-awareness skills (10%), (2) emotion management skills (20%), (3) empathy skills (20%), (4) relationship management skills (40%), and (5) responsible decision-making skills (10%). In conclusion, "karungut" is a part of the local culture of the Dayak  that can be utilized to strengthen socio-emotional education.